Effectiveness of Media Based on Local Materials in Improving Students’ Classification Skills - Amaliah Nurfajrianti (Jurnal Report of Biological Education, 2021)
Background: This study aims to determine the effectiveness of using local material-based media in improving the classification skills on the concept of Classification of Living Things. The method is a classroom action research involving 30 students of grade VII of SMPN 1 Gegerbitung. Local material-based media made from used materials such as bottle caps and colored paper. A classification test, a dichotomous classification comprehension test, and a student response questionnaire were used as instruments. Results: The average classification skills of students after using learning media based on local materials increased by 43%, however, the classification skills of students in general, were still at the beginning stage (38.31%) and an average value of 49.53. The students' classification skills increased from cycle I (49.53) to cycle II (73.30), with the average N-gain in the medium category (0.47). Student responses were very good when using the media based on local materials and also help them to understand the principles of classification, although several students still have difficulty in making the basis of grouping. The conclution of this study obtained that local material-based media was effective in improving student's classification skills as well as improving student learning outcomes and learning motivation.